OHS AS THE MOTIVATING FACTOR IN THE EDUCATIONAL PROCESS - BARÁTH, Ondrej; FESZTEROVÁ, Melánia (Trends in education, 2013)
Occupational Health and Safety (OHS) is aimed to decrease an accident and injury rate, risk assessment and precaution using progressive arrangements from practice, education and support of consciousness that leads to the complex improvement of the welfare, increasing of "culture of work" and school preparation. This contribution is oriented on the increasing requirements on safety and hygiene of work. Based on the analysis of work actions divided into work operations, movements, and acts; we may point out the possibility of creation of skills and habits as early as in schools conditions.
Keywords: education; occupational health and safety (OHS); working process; ability; habit; analysis